Antidepressant effect of stingless bee honey in chronic stress mice model - Shaheran, Anish Ameera (2024)
Chronic stress exposure can increase the risk of developing health problems including anxiety and depression. The study primarily aimed to evaluate the antidepressant effects of stingless bee honey (SBH) in chronic stress mice model on behavioural, physiological as well as histopathological parameters. Forty-nine Swiss albino female mice were divided into seven groups and underwent 28 days of chronic stress paradigm. Ultra-performance liquid chromatography (UPLC) was used to evaluate the physicochemical properties and sugar profiles of SBH samples. The behavioural assessment was assessed using an elevated-plus maze (EPM) and forced swimming test (FST). The corticosterone, serotonin, dopamine, phenylalanine in serum and BDNF in brain tissue were assessed using enzyme-linked immunosorbent assay (ELISA). The biological analysis including cresyl violet staining and immunohistochemistry analysis targeting IL-6 and IL-1β was carried out. The results showed that the physicochemical properties and sugar profiles of SBH samples met the range of Malaysian Standard (MS2683). Chronic stress exposure to the mice elevated anxiety level in EPM and SBH potentially to alleviate the depression-like behaviour in FST by reducing immobility time. Furthermore, groups treated with SBH exhibited a reduction in neurohormonal levels including corticosterone, along with elevated serotonin and dopamine, as well as increased phenylalanine in serum. SBH-treated groups also upregulated the BDNF protein expression and improved the hippocampal neuronal as well as increased the thickness layer of pyramidal and granular regions. Besides, SBH also potentially reversed the effect of chronic stress mice as observed by the IL-6 and IL-1β protein expressions. Overall, SBH has demonstrated promising potential as a dietary supplement for managing depression. These findings highlight the need for further analysis in clinical studies.